Adhesive performance of camelina protein affected by extraction conditions - Qi, Guangyan; Li, Ningbo; Sun, Xiuzhi S.; Wang, Donghai H. (My University, 2017)
Camelina protein (CP) adhesives were prepared from de-hulled camelina meal using alkaline solubilization (CP 8, CP 9, CP 10, CP 11, CP 12) and isolelectric precipitation. CP 12 had the highest protein yield with 46.22%, more than twice that of CP 8 (22.71%), indicating that extreme alkaline pH is necessary for high camelina protein solubility and protein yield. Extreme alkalinization resulted in severe molecular dissociation of camelina protein, as indicated by the appearance of a low molecular weight band (20 kDa). Compared to CP 8, CP 9, CP 10, and CP 11, CP 12 had a completely denatured protein structure with greater amounts of exposed functional groups, which is beneficial to the adhesion strength of CP 12. CP 12 with 9% sodium chloride treatment demonstrated optimum adhesion performance with dry and wet strengths of 4.36 and 1.36 MPa, respectively, compared to 3.37 and 1.05 MPa for CP 12 without sodium chloride treatment. © 2016 American Society of Agricultural and Biological Engineers.
Citation: Qi, G., Li, N., Sun, X. S., & Wang, D. (2016). Adhesive performance of camelina protein affected by extraction conditions. Transactions of the Asabe, 59(3), 1083-1090. doi:10.13031/trans.59.11686
Keywords: Adhesives; Biodegradable; Camelina Proteins; Rheology; Thermal Properties; Adhesion